A single nucleotide deletion in the third exon of FT‐D1 increases the spikelet number and delays heading date in wheat (Triticum aestivum L.). Issue 5 (29th January 2022) - Chen, Zhaoyan; Ke, Wensheng; He, Fei; Chai, Lingling; Cheng, Xuejiao; Xu, Huanwen; Wang, Xiaobo; Du, Dejie; Zhao, Yidi; Chen, Xiyong; Xing, Jiewen; Xin, Mingming; et al.
Summary: The spikelet number and heading date are two crucial and correlated traits for yield in wheat. Here, a quantitative trait locus (QTL) analysis was conducted in F8 recombinant inbred lines (RILs) derived from crossing two common wheats with different spikelet numbers. A total of 15 stable QTL influencing total spikelet number (TSN) and heading date (HD) were detected. Notably, FT‐D1, a well‐known flowering time gene in wheat, was located within the finely mapped interval of a major QTL on 7DS ( QTsn/Hd.cau‐7D ). A causal indel of one G in the third exon of FT‐D1 was significantly associated with total spikelet number and heading date. Consistently, CRISPR/Cas9 mutant lines with homozygous mutations in FT‐D1 displayed an increase in total spikelet number and heading date when compared with wild type. Moreover, one simple and robust marker developed according to the polymorphic site of FT‐D1 revealed that this one G indel had been preferentially selected to adapt to different environments. Collectively, these data provide further insights into the genetic basis of spikelet number and heading date, and the diagnostic marker of FT‐D1 will be useful for marker‐assisted pyramiding in wheat breeding.